Maternal catalase supplementation regulates fatty acid metabolism and antioxidant ability of lactating sows and their offspring - Tiantian Zhou; Bei Cheng; Lumin Gao; Fengyun Ren; Fengyun Ren; Guanglun Guo; Teketay Wassie; Xin Wu; Xin Wu; Xin Wu (Frontiers in Veterinary Science, 2022)
Introduction and methodsAs a crucial antioxidant enzyme, catalase (CAT) could destroy the cellular hydrogen peroxide to mitigate oxidative stress. The current study aimed to investigate the effects of maternal CAT supplementation from late gestation to day 14 of lactation on antioxidant ability and fatty acids metabolism with regard to the sow-piglet-axis. On day 95 of gestation, forty sows were divided into control (CON) group (fed a basal diet) and CAT group (fed a basal diet supplemented with 660 mg/kg CAT), the feeding experiment ended on day 14 of lactation.ResultsThe lactating sows in the CAT group produced more milk, and had higher antioxidant enzymes activity including POD and GSH-Px (P < 0.05), lower content of serum LDL as well as plasmic C18:3n3 content (P < 0.05). Additionally, maternal CAT supplementation improved offspring's body weight at day 14 of nursing period and ADG (P < 0.05), and regulated the antioxidant ability as evidenced by decreased related enzymes activity such as T-AOC and CAT and changed genes expression level. It significantly affected lipid metabolism of suckling piglets manifested by increasing the serum ALT, CHOL, and LDL (P < 0.05) level and modulating plasma medium- and long-chain fatty acids (MCFAs and LCFAs), as well as regulating the genes expression involved in lipid metabolism.ConclusionMaternal CAT supplementation could regulate the fatty acid composition and enhance the antioxidant ability of sows and offspring during the lactating period and further promote the growth of suckling piglets. These findings might provide a reference value for the utilization of CAT as supplement for mother from late pregnancy to lactation period to promote the fatty acid metabolism of offspring.